The role of Turkey in the world hazelnut production and exporting - Semih Uzundumlu, Ahmet; Kurtoğlu, Seval; Şerefoğlu, Coşkun (Emirates Journal of Food and Agriculture, 2022)
The aim of this study is to estimate the future of the global hazelnut sector for 2019-2025 using the data of 1961-2018. ARIMA model was used to forecast hazelnut production and export quantity. Hirschman Herfindahl Index (HHI) and Concentration Ratios (CR) have been used to determine market status. According to HHI and CR, the world hazelnut market was oligopoly in 1961-2018 and the biggest player in this market was Turkey. Because Turkey was the largest manufacturer and marketer of hazelnut in the industry, 64% of the production and 67% of the exports of world hazelnut were provided by Turkey as the average in the period 2011-2018. Turkey thus determines the world price in hazelnut. According to the concentration ratio, CR1 will be 0.63 and 0.67 in the export and production; this means that about 63-67% of the world hazelnut production and export will have been provided by Turkey from 2019 to 2025. The number of countries producing, and exporting hazelnuts has risen from 13 to 32, and 9 to 58, respectively in the past fifty-eight years in the world. According to the findings of this study, it was forecasted that the competition degree of Turkey’s hazelnut export market will decrease during the period from 2019 to 2025. The results obtained from this study will help policymakers to monitor the way for hazelnut marketing in Turkey